Catalytic graphitized silicon-carbon composite material, preparation method thereof and lithium ion battery

By catalyzing graphitization to modify the porous carbon substrate and depositing silane in its pores, the problem of volume expansion of silicon negative electrode is solved, the rate performance and energy density of lithium-ion batteries are improved, and the application needs of high-performance batteries are achieved.

CN119774602APending Publication Date: 2025-04-08SHENZHEN SOLID ADVANCED MATERIALS TECH CO LTD +1

Patent Information

Application Number
CN202510246761.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing silicon-carbon technology cannot effectively solve the huge volume expansion problem of silicon negative electrodes during charging and discharging, resulting in structural collapse and low-magnification performance.

Method used

The porous carbon substrate is catalytically graphitized by adding a graphitization catalyst, and depositing silanes in the porous carbon pores to form silicon particles, providing sufficient expansion space while covering a carbon layer on the surface of the silicon particles.

Benefits of technology

It significantly inhibits the expansion of lithium-ion batteries, improves the conductivity and cycling stability of the materials, improves the rate performance and energy density, and meets the needs of high-performance batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774602A_ABST
    Figure CN119774602A_ABST
Patent Text Reader

Abstract

The invention relates to a catalytically graphitized silicon-carbon composite material, a preparation method thereof and a lithium ion battery. The preparation method comprises the following steps: providing a porous carbon precursor, sequentially carbonizing, activating and pore-forming, pickling, washing to be neutral, passivating to remove impurities, and then crushing and grading to obtain a porous carbon substrate with the particle size D50 of 5-20 microns; adding a graphitization catalyst into the porous carbon substrate for blending, and carrying out heat treatment at 800-1000 DEG C for 2-6 hours for catalytic modification to obtain modified porous carbon; and putting the obtained modified porous carbon into a chemical vapor deposition reaction furnace, and depositing silicon particles to obtain the catalytically graphitized silicon-carbon composite material. Wherein the graphitization catalyst comprises any one or more of potassium ferrate, iron oxide, nickel oxide, boron, aluminum, titanium, Fe-Si alloy and P-Ni alloy. The graphite catalyst is added to perform catalytic graphitization modification on the porous carbon substrate, so that the energy density, the cycle life and the rate capability of the battery are remarkably improved, and the application requirements of the high-performance battery are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a catalytic graphitized silicon-carbon composite material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Due to the environmental pollution and reserve problems of fossil fuels, the country vigorously advocates the development of new energy. Among them, lithium-ion batteries as power sources have the advantages of high energy, high power density, long life and safety and reliability, and are widely used in new energy vehicles. At present, the most commonly used commercial negative electrode for lithium-ion batteries is graphite, but the biggest problem of new energy vehicles is "mileage anxiety", so higher energy density requirements are put forward for lithium-ion batteries, and the next generation of high energy density new negative electrodes are urgently needed. The silicon negative electrode has an extremely high theoretical specific capacity (4200 mAh g-1), which is ten times that of the graphite negative electrode, and the lithium desorption potential is low (≈0.4 V vs. Li|Li+), which is environmentally friendly and has abundant reserves. However, the silicon negative electrode has a fatal disadvantage, that is, the huge volume expansion (>300%) produced during the charge and discharge process, which leads to structural collapse and loss of electrical contact between the active Si nanoparticles and the copper foil; and the silicon negative electrode has low electronic conductivity (<10 -3 S cm -1 ) cannot meet the requirements of fast kinetic reactions. In order to improve the reaction kinetics of silicon materials and thus improve the rate performance of silicon negative electrodes to meet the needs of fast charging, silicon materials and carbon materials are often combined to form silicon-carbon negative electrodes to improve the overall conductivity.

[0003] The most commonly used method for silicon-carbon negative electrodes is to compound graphite and silicon through processes such as spray granulation, sand grinding, and carbon coating. However, these processes still cannot solve the inherent volume expansion of silicon negative electrodes, and the cycle life cannot be guaranteed. The gas-phase silicon-carbon technology deposits silane into a porous carbon skeleton to form a porous silicon-carbon material. Silicon is deposited in the pores of the porous carbon, giving silicon enough space to expand, thereby inhibiting expansion and improving cycle stability.

[0004] Existing silicon-carbon technology cannot solve the problem of huge volume expansion of silicon, and due to the low electronic conductivity and slow ion diffusion of silicon, the rate performance of silicon-carbon materials is poor. In addition, most of the current research directions are to improve the process of silane deposition, and the pore structure of porous carbon and the corresponding modification are not involved.

[0005] Therefore, the existing technology needs to be improved. Summary of the invention

[0006] The silicon-carbon technology in the prior art cannot solve the huge volume expansion of silicon, and due to the low electronic conductivity and slow ion diffusion of silicon, the rate performance of silicon-carbon materials is poor. Therefore, the present invention provides a catalytic graphitized silicon-carbon composite material and a preparation method thereof, and a lithium-ion battery for solving the above problems.

[0007] To achieve the above object, in a first aspect, the present invention provides a method for preparing a catalytic graphitized silicon-carbon composite material, which comprises the following specific steps: S1, providing a porous carbon precursor, sequentially performing carbonization, activation pore formation, pickling, water washing to neutrality, passivation to remove impurities, and then crushing and classifying to obtain a porous carbon substrate with a particle size D50 of 5-20 μm; S2, adding a graphitization catalyst to the porous carbon substrate and mixing them, and heat treating them at 800°C to 1000°C for 2 to 6 hours to perform catalytic modification, thereby obtaining a modified porous carbon, wherein the mass ratio of the graphitization catalyst to the porous carbon substrate is (1 to 3): 1; S3, putting the obtained modified porous carbon into a chemical vapor deposition reactor, heating it under the protection of a protective gas, introducing a silicon source gas after the temperature reaches the reaction temperature, reacting the silicon source gas so that the silicon source gas is deposited into the pores of the modified porous carbon and decomposed to form silicon particles, thereby obtaining a catalytic graphitized silicon-carbon composite material; Wherein, the graphitization catalyst includes any one or more of potassium ferrate, iron oxide, nickel oxide, boron, aluminum, titanium, Fe-Si alloy and P-Ni alloy.

[0008] In one implementation, in S3, after the silicon source gas is introduced, acetylene is introduced to obtain a silicon-carbon composite material having a surface coated with a carbon layer.

[0009] In one implementation, in S1, the porous carbon precursor includes any one of phenolic resin, furan resin, epoxy resin, polyacrylonitrile and asphalt-based precursor.

[0010] In one implementation, in S1, the activation pore formation includes any one of adding an activation pore-forming agent for activation, CO2 physical activation, and water vapor physical activation, and the activation pore-forming agent includes any one of KOH, NaOH, and K2CO3.

[0011] In one implementation, in S1, the carbonization temperature is 400°C to 700°C, and the passivation temperature is 500°C to 1500°C.

[0012] In one implementation, in S3, the pore size of the silicon-carbon composite material is 0.1-50 nm.

[0013] In one implementation, in S3, the protective gas is a non-oxidizing gas, preferably any one of nitrogen, argon, hydrogen, and a hydrogen-argon mixture; the reaction temperature is 250°C to 800°C; the silicon source gas includes any one of silane, monochlorosilane, dichlorosilane, trichlorosilane, chlorosilane, ethylsilane or monochlorosilane, or a mixture of at least two thereof; the introduction rate of the silicon source gas is 0.2L / min to 10L / min; and the reaction time is 0.5h to 6h.

[0014] In a second aspect, the present invention further provides a catalytic graphitized silicon-carbon composite material, which is prepared by the preparation method of the catalytic graphitized silicon-carbon composite material described in the present invention.

[0015] In a third aspect, the present invention further provides a lithium-ion battery, which uses the above-mentioned catalytic graphitized silicon-carbon composite material as a negative electrode.

[0016] Beneficial effects: The present invention catalytically graphitizes the porous carbon substrate by adding a graphite catalyst, thereby avoiding the current situation that graphitization can only be achieved at high temperatures, and allows graphite microcrystals to be formed below 1000°C, thereby ensuring the pore structure and improving the degree of graphitization, thereby improving the conductivity of the carbon material; by depositing silane into the pores of the porous carbon, sufficient expansion space for silicon is provided, thereby inhibiting the expansion of the lithium-ion battery; at the same time, the formation of local graphitized microcrystals can improve the lithium storage performance of the porous silicon-carbon, improve the capacity and the first coulomb efficiency, improve the stability of the overall carbon substrate, and facilitate the rapid deintercalation of lithium ions, thereby improving the rate performance of the overall material. The catalytically graphitized silicon-carbon composite material is used as the negative electrode of a lithium-ion battery, which significantly improves the energy density, cycle life and rate performance of the battery, and meets the application requirements of high-performance batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a flow chart of the steps of the method for preparing the catalytic graphitized silicon-carbon composite material provided by the present invention; Figure 2 : is the XRD pattern of the modified porous carbon provided in each embodiment and comparative example; Figure 3 1 is a Raman spectrum of the modified porous carbon provided in each embodiment and comparative example; Figure 4 It is a powder resistance test diagram of the modified porous carbon provided in each embodiment and comparative example; Figure 5 1 is a charge-discharge curve diagram of the first cycle of the modified porous carbon provided in the comparative example and each embodiment; Figure 6 It is a first cycle charge and discharge curve diagram of the catalytic graphitized silicon-carbon composite material provided in the comparative example and each embodiment.

[0018] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0020] Read more Figure 1 , Figure 1 The present invention provides a method for preparing a catalytically graphitized silicon-carbon composite material, which comprises the following specific steps: S1, providing a porous carbon precursor, sequentially performing carbonization, activation pore formation, pickling, water washing to neutrality, passivation to remove impurities, and then crushing and classifying to obtain a porous carbon substrate with a particle size D50 of 5-20 μm; S2, adding a graphitization catalyst to the porous carbon substrate and mixing them, and heat treating them at 800°C to 1000°C for 2 to 6 hours to perform catalytic modification, thereby obtaining a modified porous carbon, wherein the mass ratio of the graphitization catalyst to the porous carbon substrate is (1 to 3): 1; S3, putting the obtained modified porous carbon into a chemical vapor deposition reactor, heating it under the protection of a protective gas, introducing a silicon source gas after the temperature reaches the reaction temperature, reacting the silicon source gas so that the silicon source gas is deposited into the pores of the modified porous carbon and decomposed to form silicon particles, thereby obtaining a catalytic graphitized silicon-carbon composite material; Wherein, the graphitization catalyst includes any one or more of potassium ferrate, iron oxide, nickel oxide, boron, aluminum, titanium, Fe-Si alloy and P-Ni alloy.

[0021] In S3, after the silicon source gas is introduced, acetylene is introduced to obtain a silicon-carbon composite material with a carbon layer coated on the surface. The silicon-carbon structure provided by the present invention utilizes the voids of the porous carbon substrate to give silicon enough space for expansion, and finally coats it with a carbon layer to improve the overall conductivity and prevent direct contact between silicon particles and electrolyte, thereby reducing the generation of side reactions. By forming a carbon layer on the surface of the silicon particles, the cycle stability of the silicon-carbon composite material can be further improved, thereby improving its electrochemical performance.

[0022] Specifically, in S1, the porous carbon precursor includes any one of phenolic resin, furan resin, epoxy resin polyacrylonitrile and asphalt-based precursor. The activation pore-forming includes any one of adding an activation pore-forming agent for activation, CO2 physical activation and water vapor physical activation, and the activation pore-forming agent includes any one of KOH, NaOH and K2CO3. When the activation pore-forming agent is KOH, the mass ratio of alkali carbon for mixed activation pore-forming of carbonized material and KOH is (1.2~2.5):1. Further, the carbonization temperature is 400℃~700℃, and the passivation temperature is 500℃~1500℃. In this step, a suitable carbon source is provided, and volatile components are removed by high-temperature treatment to generate primary carbon materials; a porous structure is formed by activation pore-forming, which can increase the specific surface area of ​​the material; inorganic impurities and metal residues can be removed by acid washing and water washing, and the treated carbon material is crushed to a particle size D50 of 5~20μm, and graded to ensure a suitable particle size distribution.

[0023] In S2, when the graphitization catalyst used is potassium ferrate, further catalytic graphitization is achieved, the decomposed KOH can be used as a pore-forming agent to form pores, and the decomposed Fe2O3 can play a catalytic role to improve the graphitization degree of the material. The increase in the degree of graphitization can increase the conductivity of the overall porous carbon, thereby improving the conductivity of the overall silicon-carbon material; it can also increase more reversible lithium storage capacity at the local graphite layer, thereby improving the capacity and first coulomb efficiency of the overall porous silicon-carbon; at the same time, the increase in the degree of graphitization will cause more defects in the carbon material, making it easier for lithium ions to pass through the defects, thereby improving the ion diffusion capacity of the overall material, thereby improving the rate performance of silicon-carbon.

[0024] In this step, by adding a graphitization catalyst to catalyze graphite, the graphitization temperature is greatly reduced, and the graphitization can be completed below 1000°C, thereby avoiding the influence of high temperature on the destruction of the porous carbon pore structure. Increasing the graphitization degree while ensuring the pore structure can improve the conductivity and ion diffusion rate of the carbon substrate.

[0025] In S3, the pore size of the silicon-carbon composite material is 0.1~50nm, and the size of the silicon nanoparticles in the silicon-carbon composite material is 0.1~100nm. In S3, the protective gas is a non-oxidizing gas, preferably any one of nitrogen, argon, hydrogen, and a hydrogen-argon mixture; the reaction temperature is 250℃~800℃; the silicon source gas includes any one of silane, monochlorosilane, dichlorosilane, trichlorosilane, chloroform, ethane or monochloroethane, or a mixture of at least two; the introduction rate of the silicon source gas is 0.2L / min~10L / min; the reaction time is 0.5h~6h. By depositing silicon into the structure of the porous carbon substrate, silicon is distributed in the porous carbon pores, giving silicon enough expansion space, and silicon is in an amorphous state, anisotropic when expanding, effectively slowing down the volume expansion problem of the silicon negative electrode, so that the obtained porous silicon-carbon composite material has good cycle stability and rate performance.

[0026] The present invention is based on the graphitization improvement modification of the porous carbon substrate in the porous silicon-carbon composite material. By improving the graphitization degree of the porous carbon substrate, the conductivity of the porous carbon substrate and the electron transfer rate can be improved, and the reversible capacity of the porous carbon substrate can be improved, thereby improving the first coulombic efficiency of the porous silicon-carbon composite material.

[0027] The present invention is also illustrated by providing a number of examples and comparative examples.

[0028] Embodiment 1: S1. Preparation of porous carbon substrate: 15 kg of phenolic resin was put into a box furnace for carbonization at a carbonization temperature of 600°C. The obtained carbonized material was mixed with KOH for activation and pore formation at an alkali-carbon ratio of 2:1. The activated product was pickled and washed with water until the pH was neutral. It was passivated at a high temperature of 1000°C to remove impurities, and finally crushed and classified to control the particle size D50 at about 12um.

[0029] S2. Graphitization modification of porous carbon substrate: When the carbonized material obtained in S1 is mixed with KOH, potassium ferrate is added for catalysis to obtain modified porous carbon. The mass ratio of potassium ferrate:carbonized material:KOH is 3:1:1.5. Potassium ferrate can be decomposed to obtain KOH and Fe2O3, KOH can play an activation role, and Fe2O3 can play a catalytic graphitization effect.

[0030] S3. Preparation of CVD silicon-carbon composite material: The modified porous carbon obtained is added into a fluidized bed, and a sufficient amount of silane gas is introduced to allow it to deposit into the pores of the porous carbon, and then decompose to form silicon particles. Acetylene is then introduced to coat a carbon layer on the surface of the silicon-carbon to increase the conductivity of the material, thereby obtaining a catalytic graphitized silicon-carbon composite material.

[0031] Embodiment 2: The porous carbon base material was prepared by the same method as in Example 1. In S2, the mass ratio of potassium ferrate:carbonized material:KOH was 3:1:1.7. The other steps were the same as in Example 1 and will not be repeated here.

[0032] Embodiment 3: The porous carbon base material was prepared by the same method as in Example 1. In S2, the mass ratio of potassium ferrate:carbonized material:KOH was 3:1:1. The other steps were the same as in Example 1 and will not be repeated here.

[0033] Comparative Example 1: The porous carbon substrate material was prepared by the same method as in Example 1, and the porous carbon substrate was not graphitized and no potassium ferrate catalyst was added. The other steps were the same as in Example 1 and will not be described again.

[0034] Table 1. First cycle charge and discharge data of modified porous carbon provided in comparative examples and embodiments Table 2. First cycle charge and discharge data of the silicon-carbon composite materials provided in the comparative examples and the embodiments Results and analysis: Figure 2 : is the XRD diagram of the catalytically modified porous carbon provided in each embodiment and comparative example. Figure 2 It can be seen that the XRD curve of the comparative material is relatively flat, with basically no obvious diffraction peaks, indicating that the porous carbon without graphitization catalyst is amorphous, while Examples 1 to 3 show obvious diffraction peaks at around 26°, corresponding to the (002) peak of graphite, indicating that the modified porous carbon of Examples 1 to 3 has been significantly improved after catalysis.

[0035] Figure 3 : is the Raman spectrum of the modified porous carbon provided in each embodiment and comparative example. Figure 3 It can be seen that the ratio of the D peak to the G peak of Comparative Example 1, ID / IG, is greater than 1, indicating that the overall material has more defects and less graphitized ordered structures, while the D peaks of other embodiments are almost 0, and ID / IG is less than 1, indicating that the material has fewer defects and a high degree of graphitization.

[0036] Figure 41 is a graph showing the powder resistance of the modified porous carbon provided in each embodiment and comparative example. Figure 4 It can be seen that Example 1 with a high degree of graphitization has a smaller resistivity, indicating that it improves the overall conductivity of the material.

[0037] Figure 5 The first cycle charge and discharge curves of the modified porous carbon provided in the comparative examples and the embodiments are shown in FIG. Figure 5 As can be seen from Table 1, the first coulombic efficiency and capacity of the modified porous carbon after catalytic graphitization are improved to a certain extent.

[0038] Figure 6 The first cycle charge and discharge curves of the catalytic graphitized silicon-carbon composite material provided in the comparative examples and the embodiments are shown in FIG. Figure 6 As can be seen from Table 2, the first coulombic efficiency and capacity of the porous silicon carbon after catalytic graphitization are also improved compared with the original sample, and its lithium insertion platform is lower than that of the control example, and the lithium insertion peak of graphite appears, which has better compatibility with the subsequent composite matching of silicon carbon and graphite.

[0039] In general, the present invention catalytically graphitizes and modifies the porous carbon substrate by adding a graphite catalyst, thereby avoiding the current situation that graphitization can only be achieved at high temperatures, and allowing graphite microcrystals to be formed below 1000°C, thereby ensuring the pore structure and improving the degree of graphitization, thereby improving the conductivity of the carbon material; by depositing silane into the pores of the porous carbon, sufficient expansion space for silicon is provided, thereby inhibiting the expansion of the lithium-ion battery; at the same time, the formation of local graphitized microcrystals can improve the lithium storage performance of the porous silicon-carbon, improve the capacity and the first coulomb efficiency, improve the stability of the overall carbon substrate, and facilitate the rapid deintercalation of lithium ions, thereby improving the rate performance of the overall material. The catalytically graphitized silicon-carbon composite material is used as the negative electrode of a lithium-ion battery, which significantly improves the energy density, cycle life and rate performance of the battery, and meets the application requirements of high-performance batteries.

[0040] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a catalytic graphitized silicon-carbon composite material, characterized in that: The specific steps include: S1, providing a porous carbon precursor, sequentially performing carbonization, activation pore formation, pickling, water washing to neutrality, passivation to remove impurities, and then crushing and classifying to obtain a porous carbon substrate with a particle size D50 of 5-20 μm; S2, adding a graphitization catalyst to the porous carbon substrate and mixing them, and heat treating them at 800°C to 1000°C for 2 to 6 hours to perform catalytic modification, thereby obtaining a modified porous carbon, wherein the mass ratio of the graphitization catalyst to the porous carbon substrate is (1 to 3): 1; S3, putting the obtained modified porous carbon into a chemical vapor deposition reactor, heating it under the protection of a protective gas, introducing a silicon source gas after the temperature reaches the reaction temperature, reacting the silicon source gas so that the silicon source gas is deposited into the pores of the modified porous carbon and decomposed to form silicon particles, thereby obtaining a catalytic graphitized silicon-carbon composite material; Wherein, the graphitization catalyst includes any one or more of potassium ferrate, iron oxide, nickel oxide, boron, aluminum, titanium, Fe-Si alloy and P-Ni alloy.

2. The method for preparing a catalytic graphitized silicon-carbon composite material according to claim 1, characterized in that: In S3, after the silicon source gas is introduced, acetylene is introduced to obtain a silicon-carbon composite material with a carbon layer covering the surface.

3. The method for preparing a catalytic graphitized silicon-carbon composite material according to claim 1 or 2, characterized in that: In S1, the porous carbon precursor includes any one of phenolic resin, furan resin, epoxy resin, polyacrylonitrile and asphalt-based precursor.

4. The method for preparing a catalytic graphitized silicon-carbon composite material according to claim 1 or 2, characterized in that: In S1, the activation pore-forming includes any one of adding an activation pore-forming agent for activation, CO2 physical activation and water vapor physical activation, and the activation pore-forming agent includes any one of KOH, NaOH and K2CO3.

5. The method for preparing a catalytic graphitized silicon-carbon composite material according to claim 1 or 2, characterized in that: In S1, the carbonization temperature is 400°C to 700°C, and the passivation temperature is 500°C to 1500°C.

6. The method for preparing a catalytic graphitized silicon-carbon composite material according to claim 1 or 2, characterized in that: In S3, the pore size of the silicon-carbon composite material is 0.1-50 nm.

7. The method for preparing a catalytic graphitized silicon-carbon composite material according to claim 1 or 2, characterized in that: In S3, the protective gas is a non-oxidizing gas, preferably any one of nitrogen, argon, hydrogen, and a hydrogen-argon mixture; the reaction temperature is 250°C to 800°C; the silicon source gas includes any one of silane, monochlorosilane, dichlorosilane, trichlorosilane, chlorosilane, ethylsilane or monochlorosilane, or a mixture of at least two of them; the introduction rate of the silicon source gas is 0.2L / min to 10L / min; and the reaction time is 0.5h to 6h.

8. A catalytic graphitized silicon-carbon composite material, characterized in that: The method for preparing the catalytic graphitized silicon-carbon composite material according to any one of claims 1 to 7 is used.

9. A lithium ion battery, characterized in that: The catalytic graphitized silicon-carbon composite material according to claim 8 is used as the negative electrode.

Citation Information

Patent Citations

  • Preparation method of high specific surface area porous graphitized carbon

    CN108557816A

  • Porous carbon material and preparation method thereof, silicon carbon material, secondary battery and electronic equipment

    CN118637606A

Cited By

  • Silicon-carbon negative electrode material based on porous graphitized carbon and preparation method of silicon-carbon negative electrode material

    CN120565617A

  • Preparation of high-strength porous carbon based on rigid molecule reinforced phenolic resin copolymerization

    CN120864497A

  • Silicon-carbon negative electrode material, preparation method thereof and lithium ion battery

    CN120978051A

  • Silicon-carbon negative electrode material, preparation method thereof and lithium ion battery

    CN120978051B